The roles of epigenetic modifications in the regulation of auxin biosynthesis - Wang, Jun-Li; Di, Dong-Wei; Luo, Pan; Zhang, Li; Li, Xiao-Feng; Guo, Guang-Qin; Wu, Lei (Frontiers in Plant Science, 2022)
Auxin is one of the most important plant growth regulators of plant morphogenesis and response to environmental stimuli. Although the biosynthesis pathway of auxin has been elucidated, the mechanisms regulating auxin biosynthesis remain poorly understood. The transcription of auxin biosynthetic genes is precisely regulated by complex signaling pathways. When the genes are expressed, epigenetic modifications guide mRNA synthesis and therefore determine protein production. Recent studies have shown that different epigenetic factors affect the transcription of auxin biosynthetic gene. In this review, we focus our attention on the molecular mechanisms through which epigenetic modifications regulate auxin biosynthesis.